Comparison of Rehabilitation Outcomes for Long Term Neurological Conditions: A Cohort Analysis of the Australian Rehabilitation Outcomes Centre Dataset for Adults of Working Age. - Lynne Turner-Stokes; Roxana Vanderstay; Tara Stevermuer; Frances Simmonds; Fary Khan; Kathy Eagar (PLoS ONE)
Objective To describe and compare outcomes from in-patient rehabilitation (IPR) in working-aged adults across different groups of long-term neurological conditions, as defined by the UK National Service Framework. Design Analysis of a large Australian prospectively collected dataset for completed IPR episodes (n = 28,596) from 2003-2012. Methods De-identified data for adults (16-65 years) with specified neurological impairment codes were extracted, cleaned and divided into 'Sudden-onset' conditions: (Stroke (n = 12527), brain injury (n = 7565), spinal cord injury (SCI) (n = 3753), Guillain-Barré syndrome (GBS) (n = 805)) and 'Progressive/stable' conditions (Progressive (n = 3750) and Cerebral palsy (n = 196)). Key outcomes included Functional Independence Measure (FIM) scores, length of stay (LOS), and discharge destination. Results Mean LOS ranged from 21-57 days with significant group differences in gender, source of admission and discharge destination. All six groups showed significant change (p<0.001) between admission and discharge that was likely to be clinically important across a range of items. Significant between-group differences were observed for FIM Motor and Cognitive change scores (Kruskal-Wallis p<0.001), and item-by-item analysis confirmed distinct patterns for each of the six groups. SCI and GBS patients were generally at the ceiling of the cognitive subscale. The 'Progressive/stable' conditions made smaller improvements in FIM score than the 'Sudden-onset conditions', but also had shorter LOS. Conclusion All groups made gains in independence during admission, although pattern of change varied between conditions, and ceiling effects were observed in the FIM-cognitive subscale. Relative cost-efficiency between groups can only be indirectly inferred. Limitations of the current dataset are discussed, together with opportunities for expansion and further development.